Figurative Language in the Book of Isaiah: A Study of the Isindebele Bible (Ibhayibheli Elicwengileko) - Nomsa Skosana; Respect Mlambo (JOLLT Journal of Languages and Language Teaching, 2026)
The translation of biblical texts into South African indigenous languages was historically undertaken by missionaries who rendered scriptures from Greek and Hebrew into English and subsequently into local languages to facilitate evangelisation. Within this trajectory, isiNdebele remained marginalised and was among the last South African languages to receive a complete Bible translation, making the 2012 publication of IBhayibheli Elicwengileko both linguistically and historically significant. This context underscores the importance of examining how figurative language central to biblical meaning and interpretation is conveyed in an underrepresented African language beyond the missionary translation era. This study aims to identify, categorise, and analyse figurative expressions in relation to their contextual meaning. Employing a descriptive qualitative methodology, the study integrates Perrine’s Theory of Figurative Language with Pragmatic Theory to interpret meanings beyond literal sense, while purposive sampling isolates verses containing salient figurative usage. The analysis identified 50 similes, 38 metaphors, 34 instances of personification, 29 cases of hyperbole, 28 examples of irony, and 24 euphemisms. Findings indicate that these expressions largely preserve their connotative force in isiNdebele, demonstrating the translation’s effectiveness in maintaining figurative nuance. The study contributes to translation studies by illuminating strategies for conveying figurative meaning in underrepresented African languages, while also highlighting implications for biblical interpretation, language preservation, and the pedagogical use of indigenous-language scriptures. It also supports ongoing efforts in African language documentation, corpus development, and culturally grounded translation scholarship.